Antimicrobial Usage in Commercial and Domestic Poultry Farming in Two Communities in the Ashanti Region of Ghana - Paintsil, Ellis Kobina (Antibiotics (Basel), 2021)
Poultry farming is a common practice in Ghana. Antibiotics are used, particularly in commercial poultry farming, as growth promoters and to prevent and cure infections. However, there is little information on antimicrobial usage in domestic poultry farming in Ghana. This study aimed to describe antimicrobial usage in commercial and domestic poultry farming. A cross-sectional survey was conducted within the Ashanti region of Ghana including 33 commercial farms and 130 households with domestic poultry farming. The median poultry population on commercial farms was 1500 (IQR: 300–3000) compared with 18 (IQR: 10–25) on domestic farms. The majority (97%, n = 32) of commercial farms used antimicrobials, compared with 43% (n = 56) of the domestic farms. Commercial farmers were 6.1 (CI: 3.2–11.8) times more likely to read and follow instructions on antimicrobials in comparison with domestic poultry keepers. About 11% of domestic and 34% of commercial farmers had received education on antimicrobial usage. None of the commercial farmers used herbal remedies; however, 40% (n/N = 52/130) of domestic farmers administered herbs. The misuse of antimicrobials in domestic poultry production calls for stricter regulations and training to limit the emergence and spread of antimicrobial-resistant bacteria among poultry.